Providing international adaptation finance for vulnerable communities: a study on potentials and limits of social investment funds - Britta Horstmann; Günther Schulz-Heiss (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
Governments are currently facing the challenge of designing efficient and effective institutional arrangements that allow international adaptation funds to be delivered while meeting national and international financing requirements. Based on adaptation financing criteria and practical experience, this study looks at the potential of using social investment funds (SIFs) for channelling (international) adaptation finance to vulnerable communities. Social investment funds are known for their potential to bundle a large number of small-scale projects at the local level into national programmes. They have been used in international financial cooperation for more than 20 years and have been designed to promote a decentralised and community-driven investment approach, often targeted at disadvantaged and vulnerable groups.
Keywords: 330; Entwicklungsfinanzierung und öffentliche Finanzen; Klimawandel; Soziale Sicherung und Inklusion